2010
DOI: 10.1128/jvi.02569-09
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Encephalomyocarditis Virus and Poliovirus Replication by Quinacrine: Implications for the Design and Discovery of Novel Antiviral Drugs

Abstract: The 9-aminoacridine (9AA) derivative quinacrine (QC) has a long history of safe human use as an antiprotozoal and antirheumatic agent. QC intercalates into DNA and RNA and can inhibit DNA replication, RNA transcription, and protein synthesis. The extent of QC intercalation into RNA depends on the complexity of its secondary and tertiary structure. Internal ribosome entry sites (IRESs) that are required for initiation of translation of some viral and cellular mRNAs typically have complex structures. Recent work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Nucleic acid-intercalating drugs were shown to inhibit IRES-mediated translation more than cap-dependent translation at low concentrations (10 to 20 M) (31). It was subsequently shown that QC inhibited the IRES activities of encephalomyocarditis virus (EMCV), hepatitis C virus (HCV), and poliovirus in a dose-dependent manner by interacting with the highly complex secondary structures of their IRES regions (32). The same study also found that the cellular p53 IRES, which has a much less complex secondary structure, is not sensitive to QC (32).…”
Section: Wssv Icp35 Is a Highly Expressed Nonstructural Proteinsupporting
confidence: 51%
See 1 more Smart Citation
“…Nucleic acid-intercalating drugs were shown to inhibit IRES-mediated translation more than cap-dependent translation at low concentrations (10 to 20 M) (31). It was subsequently shown that QC inhibited the IRES activities of encephalomyocarditis virus (EMCV), hepatitis C virus (HCV), and poliovirus in a dose-dependent manner by interacting with the highly complex secondary structures of their IRES regions (32). The same study also found that the cellular p53 IRES, which has a much less complex secondary structure, is not sensitive to QC (32).…”
Section: Wssv Icp35 Is a Highly Expressed Nonstructural Proteinsupporting
confidence: 51%
“…10B). QC is presumably able to do this by virtue of its high affinity of binding to relatively complex secondary and/or tertiary structures (32). Unlike most other DNA viruses, WSSV has many gene clusters, and since these are all likely to use IRES elements to regulate translation, the same mechanism would also inhibit the translation of other important WSSV proteins encoded by these clusters.…”
Section: Discussionmentioning
confidence: 99%
“…S2). Subsequently, several compounds were used to validate these results: the anthracycline analogues DNR and EPI, the non-anthracyclines etoposide and ellipticine, and the known EV IRES inhibitor quinacrine (Gasparian et al, 2010;Wang et al, 2013) were used to treat the cells transfected with the dicistronic reporter mRNAs. The cells treated with the anthracycline analogues and quinacrine exhibited similar trends: decreasing levels of the EV IRES activities and statistically unaltered p53 IRES activities (Fig.…”
Section: Mechanism-of-action Of Idrmentioning
confidence: 99%
“…A fixed concentration of IDR (4 mM) was titrated with the EV 59 UTR RNAs and cellular p53 IRES RNA samples at 0.25-1 mM, and the fluorescence intensities were measured. Poly(rU) was used as a negative control because it is known to be unstructured with limited binding to the known nucleic acid ligands (Chaires, 2005;Gasparian et al, 2010), whereas a highly polymerized, long-stretch calf thymus DNA that efficiently binds to IDR was used as a positive control (Chaires, 2005;Charak & Mehrotra, 2013;Ozluer & Kara, 2014). EMCV 59 UTR RNA was also included for comparison.…”
Section: Idr Displays Stronger Affinities To the Ev 59 Utr Rnasmentioning
confidence: 99%
“…21,22 On the other hand, the nucleic acid-binding ligand acriflavine inhibits protein synthesis in cell free lysates with specificity for internal initiation of translation. 23 However, the efficacy of most these molecules in animal models are not well documented and their mode of action are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%